Effect of graded levels of dietary crude protein on the enteric methane emissions in growing Murrah buffalo calves - Dixit, Sonam; Keshri, Anchal; VV, Vinay; Kundu, SS (Indian Journal of Dairy Science, 2021)
The present study was done to investigate the effect of graded levels of dietary crude protein on enteric methane (CH4) production from Murrah buffalo calves. Fifteen Murrah buffalo male calves were divided into 5 groups (Av. BW=153.05) and were fed total mixed rations containing wheat straw, maize fodder and concentrate mixture in different proportions so that the dietary crude protein level was 5, 7.5, 10, 12.5 and 15% in groups T1,T2,T3,T4 and T5, respectively. The trial lasted for 30 days. Dry matter intake increased from 2.49 to 4.40 kg/d. Dry matter digestibility increased (P<0.05) from 48.64 to 61.97%. CH4 emissions decreased (P<0.05) from 34.48 to 12.73 g/kg DMI with increasing protein level in the ration. Hence, CH4 emissions were lower (12.73-12.83 g/Kg DMI) in animals fed rations containing 12.5 to 15% CP.